Answer x=6
(x-6)^2=0 using a^2-2ab+b^2=(a-b)^2, factor the expression
x-6=0 the only was an exponetiation can be 0 is when the base equals 0
move the constant to the right hand side and change its sign
ANSWER X=6
![-np-80 < 60\qquad\text{change the signs}\\\\np+80](https://tex.z-dn.net/?f=-np-80%20%3C%2060%5Cqquad%5Ctext%7Bchange%20the%20signs%7D%5C%5C%5C%5Cnp%2B80%3C-60%5Cqquad%5Ctext%7Bsubtract%2080%20from%20both%20sides%7D%5C%5C%5C%5Cnp%3C-140%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%7D%5C%20p%5Cneq0%5C%5C%5C%5Cif%5C%20p%3E0%2C%5C%20then%5C%20n%3C-%5Cdfrac%7B140%7D%7Bp%7D%5C%5C%5C%5Cif%5C%20p%20%3C0%5C%20then%5C%20n%3E-%5Cdfrac%7B140%7D%7Bp%7D)
------------------------------------------------------
![2a-5d=30\qquad\text{subtract 2a from both sides}\\\\-5d=-2a+30\qquad\text{change the signs}\\\\5d=2a-30\qquad\text{divide both sides by 5}\\\\d=0.4a-6](https://tex.z-dn.net/?f=2a-5d%3D30%5Cqquad%5Ctext%7Bsubtract%202a%20from%20both%20sides%7D%5C%5C%5C%5C-5d%3D-2a%2B30%5Cqquad%5Ctext%7Bchange%20the%20signs%7D%5C%5C%5C%5C5d%3D2a-30%5Cqquad%5Ctext%7Bdivide%20both%20sides%20by%205%7D%5C%5C%5C%5Cd%3D0.4a-6)
Answer:
the correct answer is d
Step-by-step explanation:
Answer:
See below
Step-by-step explanation:
It looks like
- AB⟂CD
- AB and CD bisect each other.